Relationship between karstification and burial dolomitization in Permian platform carbonates (Lower Khuff - Oman) - Beckert, Julia; Vandeginste, Veerle; John, Cedric M. (Elsevier, 2016)
Large breccia fabrics associated with karst constitute an important structure in massive limestone successions. The dimensions and shapes of breccia structures are controlled by the initial fracture pattern of the limestone and preferential pathways of the karstifying fluids, but subsequently breccia fabrics can also govern the migration of later fluids. Therefore, breccias are highly relevant features to capture for reservoir characterisation. Outcrop analogues for Lower Khuff units in the Middle East present in the Central Oman Mountains reveal brecciated fabrics up to 10’s of meters in diameter. These brecciated units are closely associated with dolomite bodies of late diagenetic origin.